2022
DOI: 10.1101/2022.03.06.483163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracing Diurnal Differences in Brain Anatomy with Voxel-Based Morphometry – Associations with Sleep Characteristics

Abstract: In recent decades magnetic resonance imaging (MRI) has established itself as the golden standard for studying human brain structure in health and disease. As a result, it has become increasingly more important to identify factors that may influence study outcomes and contribute to misleading conclusions. With the regional time-of-day (TOD) differences in structural brain metrics utterly neglected and several studies reporting inconsistent TOD changes on the global brain level, this work set out to investigate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Shorter photoperiods have been associated with smaller total hippocampal volumes (Miller et al, 2015) and smaller brainstem volumes (Majrashi et al, 2020). In contrast, (Zareba et al, 2024) reported an increase in GMV in the amygdala and hippocampus from morning to evening. The present study, which tracks brain and hormone dynamics at a high temporal resolution, suggests an overall decline in cortical and subcortical GMV from morning to evening-a pattern that mirrors the diurnal decrease in steroid hormones.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Shorter photoperiods have been associated with smaller total hippocampal volumes (Miller et al, 2015) and smaller brainstem volumes (Majrashi et al, 2020). In contrast, (Zareba et al, 2024) reported an increase in GMV in the amygdala and hippocampus from morning to evening. The present study, which tracks brain and hormone dynamics at a high temporal resolution, suggests an overall decline in cortical and subcortical GMV from morning to evening-a pattern that mirrors the diurnal decrease in steroid hormones.…”
Section: Discussionmentioning
confidence: 91%
“…Human MRI studies have begun to characterize the role of circadian rhythms in modulating brain structure and function. There are reports of diurnal differences in functional connectivity (Farahani et al, 2021;Orban et al, 2020), cerebral blood flow (Elvsåshagen et al, 2019), water diffusivity (Thomas et al, 2018;Tuura et al, 2021), and brain volume (Karch et al, 2019;Trefler et al, 2016;Zareba et al, 2023Zareba et al, , 2024. However, the association between circadian changes in hormone production and rhythmic changes in the brain is unclear.…”
Section: Introductionmentioning
confidence: 99%